Determining the Functional Oligomeric State of Membrane-Associated Protein Oligomers Forming Membrane Pores on Giant Lipid Vesicles - Singh, Vandana; Macharová, Sabína; Riegerová, Petra; Steringer, Julia P; Müller, Hans-Michael; Lolicato, Fabio; Nickel, Walter; Hof, Martin; Šachl, Radek (Analytical chemistry, 2023)
Several peripheral membrane proteins are known to form membrane pores through multimerization. In many cases, in biochemical reconstitution experiments, a complex distribution of oligomeric states has been observed that may, in part, be irrelevant to their physiological functions. This phenomenon makes it difficult to identify the functional oligomeric states of membrane lipid interacting proteins, for example, during the formation of transient membrane pores. Using fibroblast growth factor 2 (FGF2) as an example, we present a methodology applicable to giant lipid vesicles by which functional oligomers can be distinguished from nonspecifically aggregated proteins without functionality. Two distinct populations of fibroblast growth factor 2 were identified with (i) dimers to hexamers and (ii) a broad population of higher oligomeric states of membrane-associated FGF2 oligomers significantly distorting the original unfiltered histogram of all detectable oligomeric species of FGF2. The presented statistical approach is relevant for various techniques for characterizing membrane-dependent protein oligomerization.
Keywords: buněčná membrána; Lipids; fibroblastový růstový faktor 2; Protein Multimerization; membrány; membránové proteiny; multimerizace proteinu; lipidy; Fibroblast Growth Factor 2; Membrane Proteins; Membranes; Cell Membrane